WOMEN IN SOCCER: OVERVIEWING PREJUDICE AND STEREOTYPES IN THE GENDER'S OPTIC. (Fiep Bulletin - online, 2015)
We live in a full of prejudice society, that contrasts sexual differences, so, since childhood we learn what are the social roles for men and women. In this context, the goal of this study was investigate the interference in gender relations and the possibilities of stereotypes and prejudice in the choice and practice of soccer by women. The methodology had a phenomenological path in the interpretative dimension of humans. Twenty female players, between eighteen and forty years old, participated in this research, all of them living in Barbacena  MG. Were used, as instruments get the needed information, a semi-structured interview, direct observation and a field diary. The data was analyzed under their speeches and social manifestations, in the gender's optic. The results show that most of them received male influence to start playing soccer. All of them had passed through relatives' prejudice, mainly men; in the other hand, they've reacted positively to them. About power, it's concentrated in the coach's personality, generally a man. Is remarkable the courage these players have, insisting on playing soccer, under male's reserve. We concluded that gender questions, prejudice and stereotypes interfere in the choice and practice of the sport in Brazilian society, based in beliefs, myths and values that still discriminate these women for sexist reasons.
Keywords: female soccer players gender relations prejudice stereotypes